Better than their reputation: Enhancing the validity of contingent valuation mail survey results through citizen expert groups - Michael Ahlheim (2018)
Although contingent valuation is the dominant technique for the valuation of public projects, especially in the environmental sector, the high costs of contingent valuation surveys prevent the use of this method for the assessment of relatively small projects. The reason for this cost problem is that typically only contingent valuation studies which are based on face-to-face interviews are accepted as leading to valid results. Particularly in countries with high wages, face-to-face surveys are extremely costly considering that for a valid contingent valuation study a minimum of 1000 completed face-to-face interviews is required. This paper tries a rehabilitation of mail surveys as low-budget substitutes for costly face-to-face surveys. Based on an empirical contingent valuation study in Northern Thailand, it is shown that the validity of mail surveys can be improved significantly if so-called Citizen Expert Groups are employed for a thorough survey design. © 2010 University of Newcastle upon Tyne.